“The Musical” Courses Applied for Teaching the Popular Singing Major Students at Xi’an Conservatory of Music in Shaanxi Province of China” - Haidan , Cao; Banchongsilpa, Orawan (Journal of Modern Learning Development, 2023)
"The Musical" is a modern stage comprehensive art form in three aspects: vocal music, dance, and performance. The objectives of this article were to propose "The Musical" to be "The Musical" course put in the popular singing curriculum for Teaching the students majoring in popular singing at Xi’an Conservatory of Music, Shaanxi Province, China. The teaching popular in China is to use the imported form of the western musical to express the Chinese people’s life and emotion according to the Chinese people’s aesthetic habits and contemporary performance techniques, that is, to localize the music script. China’s musical plays are based on China’s local history or new creation stories, and the musical works of local people are taken as the starting point. Music styles, choreography, and dance beauty absorb the essence of Western musical drama. It is not a real "The Musical" course. A new course, "The Musical," in the curriculum would help the popular singing students have more abilities in popular singing, in acting, more professional, and more interesting, especially, the teaching would be more effective.